Sistem Manajemen Wisata Museum Kayu Tuah Himba di Kabupaten Kutai Kartanegara: Management System of Kayu Tuah Himba Museum in Kutai Kartanegara District - Risa Maulidya Araffa (Program Studi Ilmu Pemerintahan Fisip Universitas Mulawarman, 2020)
The purpose of this research is to determine the tourism management system of Kayu Tuah Himba Museum in Kutai Kartangera District, promoted as a tourism destination, and aiming at contributing to community education and regional development. Results of this research show that the tourism management system of Kayu Tuah Himba has been implemented through stages of planning, organizing, actuating, and controlling. In terms of actuating, however, the museum focuses on destination promotion without considering necessary allied tourism infrastructure like road access, accommodation, and quality of human resources to manage the museum. The existence of such inhibiting factors also affects the development programs of the museum, like the lack of financial support from the district government. Keywords: management system, museum, Kayu Tuah Himba, Kutai Kartanegara